The Effect of Return on Equity, Capital Adequacy Ratio and Financing to Deposit Ratio on Return on Assets of PT. Bank Muamalat Tbk - Khairi, Mhd Rizki; Atika; Rahmani, Nur Ahmadi Bi (Yayasan Sinergi Kawula Muda, 2024)
The aim of this study is to analyze the impact of Return on Equity (ROE), Capital Adequacy Ratio (CAR), and Financing to Deposit Ratio (FDR) on the Return on Assets (ROA) in PT. Bank Muamalat Tbk. Quantitative approaches are used using secondary data. The data collection process involves the analysis of quarterly financial reports published by P.T. Bank Muamalat in the period 2014-2023. The researchers analyzed the loss report, the financial position report and the calculation report of the minimum capital provision obligation. Statistical analysis is carried out using the SPSS version 29 program, where double linear regression methods are applied to data processing. The results of statistical analysis based on Test F show that at a 95% confidence level (α = 0.05), the variables ROE, CAR, and FDR together or simultaneously have a significant influence on ROA. The research hypothesis states that the independent variable has a significant impact on Return on Assets (ROA) as a dependent variable. From the results of the T test, the ROE variable has a significant effect on ROA of PT Bank Muamalat Tbk, while the CAR and FDR variables have no effect on ROA of PT Bank Muamalat Tbk. The estimate model yielded R values of 0.993 and R square of 0.986. This suggests that there is a very significant correlation between the free and the bound variables, where 98.6% of the changes in the binding variables can be explained by the free variables in this model. As for the other 1.4% affected by aspects not covered in the model.